Algorithms for network service guarantee under minimal link usage information - Hong, Sugwon (2006)
One way to guaranteeing service for an application flow even if a network happens to fail is to establish a restoration path with the bandwidth that amounts to the same of the flow. If the flows can share the bandwidth for their restoration paths with others, we can reduce bandwidth consumption required for restoration. It is also required that deciding sharable bandwidth among flows should be done using controllable link information at each node. This paper proposes an algorithm to determine the sharable bandwidth among application flows given local link usage information at each node, validates the results of the algorithm and analyze the conditions required to achieve the goal by simulation.